Perlindungan Hukum Terhadap Hak-Hak Pekerja Lepas Dalam Perkembangan Gig Economy di Indonesia - Komang Ayu Tri Aryani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This rapid expansion of the gig economy in Indonesia has fundamentally transformed employment relations and raised critical legal issues concerning the protection of freelance workers’ rights. Digital platform-based work offers flexibility and efficiency, yet it simultaneously creates legal uncertainty due to the absence of clear employment status and adequate labor protections. Existing labor regulations, particularly Law Number 13 of 2003 on Manpower and Law Number 11 of 2020 on Job Creation, remain largely oriented toward traditional employment relationships and have not fully accommodated the unique characteristics of gig work. As a result, freelance workers often face unequal contractual positions, limited access to social security, and insufficient legal remedies. This study employs a normative legal research method with statutory and conceptual approaches to analyze the adequacy of current legal frameworks in protecting gig workers’ rights. The findings indicate the need for a legal reconstruction that emphasizes functional employment relations, strengthens state oversight, and integrates flexible yet protective regulatory mechanisms. Such an approach is essential to ensure legal certainty, distributive justice, and sustainable labor protection within Indonesia’s evolving digital economy.